2011
DOI: 10.1186/1471-2334-11-180
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and poverty: a prospective population-based study among children in Brazil

Abstract: BackgroundChildren in developing country suffer the highest burden of pneumonia. However, few studies have evaluated associations between poverty and pneumonia.MethodsA prospective population-based study on pneumonia was carried out as part of the Latin America Epidemiological Assessment of Pneumococcus (LEAP study). Chest x-rays were obtained for children one to 35 months old with suspected pneumonia presenting to emergency care centers and hospital emergency rooms in Goiania, Brazil. Chest radiographs were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
6
39
3
3
Order By: Relevance
“…The mean WBC count was 15784/mm 3 . CBC differential was available for 266 patients and showed a mean ANC of 10886/mm 3 .…”
Section: Laboratory Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean WBC count was 15784/mm 3 . CBC differential was available for 266 patients and showed a mean ANC of 10886/mm 3 .…”
Section: Laboratory Resultsmentioning
confidence: 99%
“…The mean WBC count was 15784/mm 3 . CBC differential was available for 266 patients and showed a mean ANC of 10886/mm 3 . CRP was measured on 215 patients (80.2%); it had a mean of 10.7 mg/dl.CRP increased with increasing duration of symptoms (p< 0.05).…”
Section: Laboratory Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) In Brazil, a continental country with wide cultural, social, economic and environmental diversity, pneumonia is always one of the main causes of hospitalizations. (7) For this reason, it is important to consider environmental and climate influences in the hospital morbidity profile of this problem. (6) A study conducted in the United States observed higher rates of outpatient services (between 32.3 and 46.9 per 1,000) for bacterial pneumonia among children younger than five years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to malnutrition, a dense home environment can increase the spread of viruses and bacteria that indicate unhealthy home quality thereby contributing to an increased risk of childhood pneumonia (Thorn, 2011). Environmental conditions are an important component in the process of the occurrence of public health disorders.…”
Section: The Association Between Indoormentioning
confidence: 99%